Razlogi za obnovo postopka v individualnih delovnih sporih - Pogorelčnik Vogrinc, Neža (Delavci in delodajalci, 2016)
The act of reopening the proceedings is a means of extraordinary judicial review, which sets aside the final decision passed in the earlier procedure, enables its reopening and the issuance of a new court decision. But reopenning the proceedings may be permitted only under conditions exhaustively listed in the Civil Procedure Act. The Article deals with the application of those reasons to reopen the proceedings as applied in individual labour disputes.
Keywords: delovni spor; revizija; sodne odločbe; sodni postopek